2018
DOI: 10.1111/vsu.12781
|View full text |Cite
|
Sign up to set email alerts
|

Duty hours restriction for our surgical trainees: An ethical obligation or a bad idea?

Abstract: To ensure patient safety and protect the well-being of interns and residents, the Accreditation Council for Graduate Medical Education (ACGME) issued guidelines in 2003 limiting the working hours of physician trainees. Although many supported the goals of the ACGME, institutions struggled to restructure their programs and hire staff required by this unfunded mandate. Numerous studies have analyzed the effects of duty hours restrictions on patient outcomes and physician training over the past 15 years. Most agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…However, the majority of those surveyed reported that they are in favor of more formal proficiency assessment. Several assessment scales have been developed for proficiency assessment on clinical cases, cadavers, and simulators in human surgery; however, no assessment scale has been proved superior to any other . A validated veterinary surgery assessment scale has not yet been developed for arthroscopic skills assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of those surveyed reported that they are in favor of more formal proficiency assessment. Several assessment scales have been developed for proficiency assessment on clinical cases, cadavers, and simulators in human surgery; however, no assessment scale has been proved superior to any other . A validated veterinary surgery assessment scale has not yet been developed for arthroscopic skills assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Several assessment scales have been developed for proficiency assessment on clinical cases, cadavers, and simulators in human surgery; however, no assessment scale has been proved superior to any other. 44,45 A validated veterinary surgery assessment scale has not yet been developed for arthroscopic skills assessment. Development and use of an adapted assessment scale for simulation training and for clinical cases would permit standardization of program evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with ACGME-I working hours rules 14 had positive effects on the residents’ lifestyle, satisfaction level with clinical learning, and education without any adverse effects on their operative experience. 28 31 . Adherence to the ACGME-I rules among HMC residents has previously been associated with improved examination and research performance.…”
Section: Discussionmentioning
confidence: 99%
“…7,[62][63][64] Changing these regulations may be impeded by cultural norms and concerns about discontinuity of care, apprehension of the possibility of reduced case exposure affecting resident training, fiscal concerns, and insufficient evidence of reductions in medical error rates or resident stress in some studies. 3,40,[65][66][67][68] Long working hours during clinical training programs have traditionally been considered inevitable to ensure competency and instill professionalism. Surgeons have voiced concerns about possible compromise in the quality of resident training and operative experience if working hours are limited during the set number of years assigned to the program.…”
Section: Regulations Of Physicians' Schedule In the United Statesmentioning
confidence: 99%
“…Too often, hospital systems rely on fatigued clinicians and trainees to cover services without assessing potential impairment. [2][3][4] While this topic is poorly discussed in veterinary-specific literature, veterinary surgeons should understand how fatigue affects their capabilities and patient safety. The objective of this review is to summarize the evidence documenting the impact of occupational sleep insufficiency on functions relevant to veterinary surgeons such as work performance, patient safety, and team dynamics.…”
Section: Introductionmentioning
confidence: 99%